Combined ion exchange and adsorption equilibria of 5′‐ribonucleotides on the strong acid cation exchange resin NH‐1. Issue 7 (17th February 2017) - Jiao, Pengfei; Wu, Jinglan; Wang, Yingying; Zhou, Jingwei; Zhuang, Wei; Chen, Yong; Liu, Dong; Zhu, Chenjie; Ying, Hanjie
Abstract: BACKGROUND: 5′‐ribonucleotides including uridine 5′‐monophosphate (UMP), adenosine 5′‐monophosphate (AMP), cytidine 5′‐monophosphate (CMP), and guanosine 5′‐monophosphate (GMP) have been widely used as food additives. Ion exchange is a potential technique to separate 5′‐ribonucleotides. A knowledge of uptake equilibrium on ion exchangers is important for the design and scale‐up of ion exchange processes. The uptake equilibria of 5′‐ribonucleotides and Na + on the strong acid cation exchange resin NH‐1 were studied experimentally and modelled in binary and multicomponent systems. The uptake mechanism and thermodynamics were also studied. RESULTS: A m odified Helfferich model was developed combining ion exchange of cations with adsorption of zwitter ions. The model can predict the uptake equilibria of 5′‐ribonucleotides and Na + successfully in multicomponent systems. The hydrophobicity of bases of 5′‐ribonucleotides determined their relative affinities to the resin. The resin shows the strongest affinity for AMP among 5′‐ribonucleotides. The uptakes of 5′‐ribonucleotides cations is an endothermic and entropy‐driven process. CONCLUSION: The equilibrium model proposed is important for simulation and design of the dynamic separation process of 5′‐ribonucleotides. UMP, GMP, and CMP can be separated based on their difference in isoelectric point. AMP and CMP with similar isoelectric point can be separated based on their difference in affinity to the resin. © 2016 Society of Chemical Industry